Curious George plants a tree - Perez, Monica; Hines, Anna Grossnickle; Rey, H. A. (Hans Augusto), 1898-1977. (Boston : Houghton Mifflin, 2009)
The mischievous monkey learns about protecting the environment by planting trees and recycling paper. Includes tips on conserving energy and resources.
"With 20 Kid-Friendly Tips for a Greener World."
Keywords: Environmental protection -- Fiction; Recycling (Waste) -- Fiction; Trees -- Fiction; Monkeys -- Fiction